The Preservation and Reincarnation of Sid-Lin Monastery - Hao, Li (ICONARCH International Congress of Architecture and Planning, 2014)
Side-lin Temple is located in the old city of Lhasa. Located 100 meter west to the intersection of East Beijing Road and Danjie-lin Road and enclosed by circumambient newer constructions, the remaining ruins is only accessible through some alleys to the yard.. The temple is believed to be relocated to the present spot from Ramoche area under the 7th Dalai Lama’s rulership. During its 260 years of history, the temple suffered from periodic destructions and reconstruction. As a result, the main temple fell from the majestic edifice of 5th Reting Rinpoche to obsolescent ruins surrounded by a residence area. Dysfunction of religion, urbanization and transformation of districts’ context all contributed to the decline of Side-lin Temple. In 1984, peripheral underused monk dormitories were allotted to homeless citizens or families in bad dwelling condition. A unique remains-centered residential community was established. Similar transition occurred to other temples in the old city, such as Tsomon Ling and Moru Temple: parts of the sacred precincts were turned into secular places. However, with monks operating regular ceremonies and devotees continually worshiping idols, their main buildings retain the Buddhist functions. Side-lin Temple represents a different result. In order to carry on the preaching, the former Buddhist organization has to be resettled in other temple. With the demolished temple and the cease of religious practice, the site was given a completely different mission: to become to gathering place for the community life. Dwellers tried to strike a subtle balance between their awe to the relic and their own daily convenience. Pine branches are burned each week in the antiquated stove as part of praying, but circumambience of the stove was barricaded by household garbage. Old people are garrulous about ancient taboos, while kids like to climb into the personal bedroom of Reting Rinpoche. All these conflicting phenomena prompt me to address a few questions in my paper. How can the spiritual layer of Side-lin ruins be restored and still preserve a balance between the religious and secular lives in this area? How to rejoin the temple site with the neighborhood? How can the adjustment of the site and neighborhood adapt to the city under significant transformation? Side-lin Temple deserves better regulations instead of today’s unsupervised situation. In the mean time, a simple rehabilitation would not be a great solution because of the intertwined relationship between the relic and the neighborhood developed in the last decades. Through intensive on-site research, interview, and speculative design, I try to shed a new light on the, history, current context, and future development of Side-lin Temple, which hopefully will lead to a holistic solution for preservation and revitalization of this important historic site.